Substance Abuse among Residents of Gwagwalada Abuja, Nigeria - , A. M. Umarudeen; , O. N. Okoli; , J. Mundi; , E. Mitaire-Idonor; , E. O. Moore; , E. Adah (Archives of Current Research International, 2023)
Aims: To determine the variety of psychoactive substances existing in Gwagwalada and the extent to which residents indulged in them. Study Design: A cross-sectional survey using questionnaires and audio interviews on eligible respondents. Place and Duration of Study: Gwagwalada, Abuja, Federal Capital Territory in the month of April 2023. Methodology: A cross-sectional survey was carried out by administering pre-tested questionnaires and audio interviews on 320 respondents with substance use history from selected areas of the town using convenience sampling. Results: 100 questionnaires were returned filled, and 91 valid responses consisting of 52 (57.1%) users and 39 (42.9%) non-users were obtained. 27 (29.7%) and 25 (27.4%) of valid responses indicated active and inactive substance users, respectively. 17 (18.7%) active users frequently, and 35 (38.5%) infrequently indulged in substance abuse.Twenty (22.0%) substance users concurrently used multiple substances while 32 (35.2%) indulged in only one item per time.Most listed substances by responders and their routes of administration were alcohol (51.6%) oral, marijuana (24.2%) oral/inhalation, Crystal Methamphetamine (4.4%) inhalation/injection, Tranq (4.4%) injection, MDMA (4.4%) oral/injection, Panadol (3.3%) oral, Caffeine (3.3%) oral, Tramadol 2.2%) oral, and Datura spp. seed/leaf (2.2%) oral/smoking.Most used routes were oral (79.1%), inhalation/smoking (35.2%), and injection (28.2%). Alcohol was the substance most concurrently used with other listed substances, but mostly with marijuana and tramadol.Reasons given by respondents for their indulgence are peer pressure (42%), recreational use (30%), as a therapy (22%), to feel good (4%), and nonsensical reasons (2%). Responders listed availability/ accessibility, affordability, peer pressure, need to belong, as coping mechanism with the harsh economic realities as factors promoting substance abuse. Conclusion: Our findings of Crystal Methamphetamine, Tranq, MDMA and Datura species among the variety of psychoactive substances and the fact that 29.7% of the sampled population actively indulged in them indicates a high prevalence of substance abuse Gwagwalada. This calls for urgent substance abuse mitigation strategies.